The Development of a Pop-Up Book with the Theme ‘Einkaufen’ as a German Language Learning Medium for Grade XI Students at SMA Negeri 3 Binjai (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to develop a pop-up book learning medium with the theme “Einkaufen” (Shopping) as a German language instructional medium for Grade XI students at SMA Negeri 3 Binjai. The background of this study is the low level of students’ understanding of the learning materials and their lack of learning motivation due to the use of monotonous conventional media. This research employs a Research and Development (R&D) approach using the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The results of the implementation stage indicate that 98.3% of students agreed that the pop-up book is effective for use in German language learning, and 96.7% stated that the material content is easy to understand. The pop-up book consists of six pages containing learning materials and exercises that focus on reading, writing, and speaking skills. Validation by material and media experts yielded a score of 90, categorized as very good. These findings demonstrate that the developed pop-up book medium is not only visually engaging but also capable of enhancing students’ motivation and comprehension in an integrative German language learning process. This medium can serve as an effective alternative for improving the quality of foreign language learning at the secondary school level.